Personality and Peripartum Changes in Perceived Social Support: Findings From Two Prospective-Longitudinal Studies in (Expectant) Mothers and Fathers - Asselmann, Eva; Garthus-Niegel, Susan; Martini, Julia (Frontiers in Psychiatry, 2022)
The aim of this study was to examine changes in perceived social support from early pregnancy to two years postpartum and to test whether these changes (a) differ between mothers and fathers or (b) vary as a function of the Big Five personality traits. Background: Higher peripartum social support in (expectant) mothers and fathers has been associated with fewer complications during pregnancy and delivery as well as better parental and offspring health. Methods: Prospective-longitudinal data from two regional-epidemiological samples from Germany were used: MARI (N=396, including n=293 mothers and n=103 fathers) and DREAM (N=2,819, including n=1,689 mothers and n=1,130 fathers). The Big Five personality traits were assessed during pregnancy in MARI as well as 8 weeks after the anticipated birth date in DREAM with short forms of the Big Five Inventory. Perceived social support was assessed during pregnancy, 4 months postpartum, and 16 months postpartum in MARI as well as during pregnancy, 14 months postpartum, and 2 years postpartum in DREAM using the short version of the Social Support Questionnaire. Results: Multilevel analyses revealed that perceived social support decreased across the peripartum period, and this decrease did not differ between mothers and fathers. More extraverted, emotionally stable, agreeable, conscientious, and open parents perceived higher levels of social support across the peripartum period. The peripartum decrease of perceived social support was smaller in parents who were more extraverted. Conclusion: Our findings suggest that especially extraversion plays an important role for high and stable levels of perceived social support across the peripartum period. Implications: Particularly highly introverted parents might profit from targeted social support interventions.